Efforts To Improve Dancing Skills in Traditional Dance Materials Using Peer Tutoring Methods at SD Negeri Pangenrejo 1 - Ade Ferliana Putri; Yuli Widiyono (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
The purpose of this research was to improve the students' traditional dancing skills and to find out the implementation of the peer tutoring method. Based on the literature review and previous research journals, the use of peer tutoring methods can be used in solving learning problems in the classroom, so the researchers are interested in conduresearchingimplementation of the method. The peer tutoring method can improve the students' dancing skills. In the pre-cycle, the average score was 50.78, then in the first cycle 64.28, and the second cycle, the average score was 83.46. The results showed that in the pre-cycle activity, the students' dancing ability had not yet reached the minimum completeness criteria, then the first cycle was held by appointing 2 students as tutors based on their values ​​in the pre-cycle and their ability of dancing. In the pre-cycle, the average result was 50.78, which was still far from the specified criteria, then the peer tutoring method was applied in the first cycle, which got an average score of 64.28, this value also still did not reach the minimum completeness criteria (KKM). Then after reflecting on the first cycle, the second cycle was implemented, which was the average score was 83.46 and had reached the KKM. This shows that the application of peer tutoring methods can improve students' traditional dancing skills.